Transition management: Guiding principles and applications. - Wittmayer, Julia M.; Steenbergen, Frank van; Frantzeskaki, Niki; Bach, Matthew (Springer, 2018)
This chapter describes a way of influencing sustainability transitions, namely transition management, and its strengths and limitations as a framework for strategic environmental planning in cities. This includes a description of the guiding principles of transition management, their translation into a governance framework and the operationalization thereof into process guidelines. For each phase of the process, rationale and methods as well as outcomes are outlined.
Keywords: Nachhaltige Stadtentwicklung; Umsetzung; Kooperation; Akteur; Transformation; Nachhaltigkeit; Management; Steuerung; Implementation; Transition